Exploring the relationship between exchange rate misalignment uncertainty and economic growth in South Africa - Eugene Msizi Buthelezi (Cogent Economics & Finance, 2023)
This paper aims to address the relatively limited attention given to the examination of exchange rate misalignment uncertainty in the specific context of South Africa. By specifically focusing on exchange rate misalignment uncertainty, this study fills a crucial gap in the literature and gains a deeper understanding of the factors influencing economic growth in South Africa. While previous literature has provided valuable insights into the relationship between exchange rate uncertainty and economic growth, there is a dearth of studies focusing on the particular issue of exchange rate misalignment uncertainty in South Africa. Therefore, the objective of this research is to investigate the effects of exchange rate misalignment uncertainty on short-term and long-term economic growth in South Africa. To achieve this objective, we employ the generalized autoregressive conditional heteroskedasticity (GARCH) and vector error correction (VEC) models. The analysis utilizes quarterly data spanning from the first quarter of 1960 to the third quarter of 2022. The findings of this study reveal a negative association between exchange rate uncertainty and short-term economic growth, while the long-term effects yield mixed results. Moreover, we observe that higher exchange rate misalignment is linked to positive implications for economic growth. These findings emphasize the significance of managing exchange rate volatility and reducing uncertainty to ensure economic stability and foster long-term growth. Considering these findings, policymakers should prioritize implementing strategies that promote a stable exchange rate and cultivate a favorable business environment.
Keywords: C82; E02; E60; E62; 330; economic growth; exchange rate; exchange rate misalignment; exchange rate misalignment uncertainty; exchange rate uncertainty